Quality of healthcare in the aftermath of the Covid-19 pandemic - Moumtzoglou, Anastasius, 1959- (Medical Information Science Reference, 2022)
"The book examines the massive stress on healthcare professionals' formal training, their creed to no harm, and the patient safety movement during the recent Covid-19 pandemic and offers suggestions on how healthcare professionals might provide their services differently "--